ARANSEMEN MUSIK PENGIRING NYANYIAN LITURGI JADI SAKSIMU ETNIS ALOR-PANTAR DI PROVINSI NUSA TENGGARA TIMUR - Hendrik Lenama (Tambur : Journal of Music Creation, Study and Performance, 2021)
The song of the Alor-Pantar inculturation workshop is a liturgical worship song that reflects the music and culture of Alor-Pantar. In May 2002 in Kalabahi there was an ecumenical collaboration between an evangelical Christian church in Timor and the liturgical music center in Yogyakarta. The musical accompaniment of the workshop songs used traditional musical instruments from Alor Regency, namely Gong, Tambur and added with piano instruments to determine the basic tone of the song and provide melody and harmonization to the song. Gong and drum instruments are traditional musical instruments from Alor district which are usually used to accompany traditional dances, pick up guests, demolish traditional houses and other traditional events. The character of the gong musical instrument is enthusiastic, builds an atmosphere of joy and joy. Gong Alor is played by striking, each gong has a different rhythmic pattern, but when combined or beaten simultaneously, it will sound so beautiful and make the atmosphere cheerful. Gong Alor is a melodic rhythmic musical instrument, but has a rhythmic function. Based on the description above, the writer wants to arrange music accompaniment to the Alor-Pantar inculturation workshop song with traditional musical instruments from Alor, namely Gong, Tambur and added with modern musical instruments, namely the piano. This musical accompaniment arrangement is poured into a thesis entitled "Music Arrangement to Accompany the Chanting of the Liturgy to Become Your Witness of the Alor-Pantar Ethnicity in East Nusa Tenggara Province".